PGA1-induced apoptosis involves specific activation of H-Ras and N-Ras in cellular endomembranes - Anta, Berta; Pérez Rodríguez, A; Castro, J; García Domínguez, Carlota A.; Ibiza, S; Martínez, N; Durá, LM; Hernández, S; Gragera, T; Peña Jimenez, Daniel; Yunta González, Mónica; Zarich, Natasha; et al. (My University, 2016)
The cyclopentenone prostaglandin A1 (PGA1) is an inducer of cell death in cancer cells. However, the mechanism that initiates this cytotoxic response remains elusive. Here we report that PGA1 triggers apoptosis by a process that entails the specific activation of H- and N-Ras isoforms, leading to caspase activation. Cells without H- and N-Ras did not undergo apoptosis upon PGA1 treatment; in these cells, the cellular demise was rescued by overexpression of either H-Ras or N-Ras. Consistently, the mutant H-Ras-C118S, defective for binding PGA1, did not produce cell death. Molecular analysis revealed a key role for the RAF-MEK-ERK signaling pathway in the apoptotic process through the induction of calpain activity and caspase-12 cleavage. We propose that PGA1 evokes a specific physiological cell death program, through H- and N-Ras, but not K-Ras, activation at endomembranes. Our results highlight a novel mechanism that may be of potential interest for tumor treatment.